Al-Isytiqaq dalam Bahasa Arab - Beti Mulu (Al-'Adl, 2009)
The title of this article is derivation (al-isytiqaq) in the Arabic. This article discusses the morphology which is one part linguistic it was known isytiqaq (derivation).Isytiqaq is derivation proses of a word from the native word to appropriate the meaning and the range of the letter but different in its form. This isytiqaq belong to the condition is the word self is native because derivation is the part was taken from the other word, is letter suitable with the native and belong the meaning appropriate.The derivation native according to the Muslim scholars of Basrah was a verbal noun (Masdar) and verb from the verbal noun, but the Muslim scholars of Kufi were contrary it. That the Ishtiaq was from the verb form.Isytiqaq in the Arabic consist of the little derivation (isytiqaq sagir) it essential who derivated from verb or noun, the big derivation (isytiqaq kabir) is the process of the word form with the change it letters position. The bigger derivation (isytiqaq akbar) is the formation of the word which the change essential of the balance word, but the letter range not change. The biggest derivation (isytiqaq kubbar) is the formulation of two words or more of them or one sentence  to one new expression which indicate the composition of its native meaning